PENGARUH ULASAN PELANGGAN ONLINE DAN SELEBRITI ENDORSEMENT TERHADAP NIAT MEMBELI (Studi tentang Scarlett Whitening dengan Kepercayaan sebagai Moderasi) - Kartika Chandra Puspita; Imronudin Imronudin (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of Online Customer Reviews and Celebrity Endorsements on Purchase Intention of local Indonesian skin care (Scarlett Whitening) moderated by Trust. This study uses a quantitative approach. The sample in this study were people aged 15-50 years who knew and understood about Scarlett Whitening skincare. The data collection used in this study uses Structural Equation Modelling (SEM) with the help of SmartPLS software version 3.2.0. The results in this study indicate that Online Customer Reviews has a positive and significant effect on Purchase Intentions and Celebrity Endorsements have a positive and significant effect on Purchase Intentions. But Trust does not moderate the effect of Online Customer Review on Purchase Intention and Trust does not moderate the effect of Celebrity Endorsement on Purchase Intention.